2000
DOI: 10.1034/j.1600-0838.2000.010002090.x
|View full text |Cite
|
Sign up to set email alerts
|

A 7‐year study on risks and costs of knee injuries in male and female youth participants in 12 sports

Abstract: Knee injuries are common and account in various sports for 15-50% of all sports injuries. The cost of knee injuries is therefore a large part of the cost for medical care of sports injuries. Furthermore, the risk of acquiring a knee injury during sports is considered higher for females than for males. The nationwide organization "Youth and Sports" represents the major source of organized sports and recreation for Swiss youth and engages annually around 370000 participants in the age group of 14 to 20 years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(153 citation statements)
references
References 0 publications
3
144
0
6
Order By: Relevance
“…Previous studies reported that there is no tendency for the age of ACL injury occurrence. [19,20,21,22] The results of this study demonstrated that man's had a 5.3-fold greater incidence rate of ACL injuries than did females. Previous studies have also reported gender differences in the incidence risk of ACL injury.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies reported that there is no tendency for the age of ACL injury occurrence. [19,20,21,22] The results of this study demonstrated that man's had a 5.3-fold greater incidence rate of ACL injuries than did females. Previous studies have also reported gender differences in the incidence risk of ACL injury.…”
mentioning
confidence: 65%
“…[19] reported that the combined number of anterior and posterior cruciate ligament injuries was 357 in boys and 113 in girls among participants in sports activities aged between the 20 to 30 years (63.5%). Even though our data focused only on ACL injuries.…”
mentioning
confidence: 99%
“…One possible explanation is the difference in sport participation. Although several studies have established that female athletes have a higher prevalence of knee injuries than their male counterparts, male participation in sports with higher collision forces (eg, football) may put them at greater risk for serious knee injuries, including multiligament and other knee dislocation injuries [3,7,13,15]. Since this dataset does not include the mechanism of injury, the number of patients who sustained their injury in sports is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, in a mixed sample (77.8% Ͻ age 19), 55.1% of basketball injuries were sprain/strains [28]. In a more in-depth analysis of knee injuries, de Loës et al [30] found that in boys 21% of knee injuries were meniscal tears, 19% were ACL/posterior cruciate ligament (PCL) ruptures, 10% were medial/lateral collateral ligament tears and 32% were nonspecific ruptures. However, for girls, only 13% were meniscal tears with 18% ACL/PCL ruptures but 21% were medial/lateral collateral ligament tears.…”
Section: Injury Severitymentioning
confidence: 99%
“…A comparison of injury rates from prospective and retrospective research is shown in table 1 and covers high school [14][15][16][17][18][19][20][21], physical education class [22], clubs/sports organizations [23][24][25][26][27], and hospital emergency departments [28,29]. In addition, studies reporting incidence data specifically for knee [18,19,30], ankle [31,32], head [33], and orofacial [34][35][36] injuries are listed. Unfortunately, the injury literature on youth basketball suffers from a broad range of methodological shortcomings, including widely varying definitions of a reportable injury, limited measures of exposure, differing metrics of risk, and poor delineation of the population at risk.…”
Section: Incidence Of Injurymentioning
confidence: 99%